The Value of Core and Noncore Activity Fit for Corporate Social Responsibility: An Expectation-Based Study of Nonprofit Hospitals. Issue 2 (April 2023) - Mathras, Daniele; Grinstein, Amir; Young, Gary J.; Thai, Ngoc H.; Young, Spencer B.
Corporate social responsibility (CSR) fit is the congruence between an organization's CSR and core activities. Previously, researchers have typically studied CSR fit as a single dimension, often finding that high-fit CSR is more effective than low-fit CSR for for-profit firms. The current research distinguishes between two dimensions of CSR fit—CSR that fits with core or noncore organizational activities—to uncover how the magnitude of investment in each type of CSR affects customer satisfaction. The authors examine the valuable and understudied context of nonprofit organizations, specifically hospitals. Results of a six-year study of over 1, 500 nonprofit hospitals suggest that noncore activity CSR positively predicts customer satisfaction, but core activity CSR does not. These findings are best explained using expectation-based theories (expectancy violation and disconfirmation): customers likely expect core activity CSR from hospitals (e.g., charity care for uninsured patients) but are delighted by noncore activity CSR (e.g., green-space renovations). In addition, noncore activity CSR becomes even more important for customer satisfaction for more affluent hospitals, whereas core activity CSR becomes increasingly important for hospitals when the community socioeconomic status is low. These nuanced results provide guidance for hospitals regarding specific CSR investment strategies that ultimately impact downstream financial reimbursements.